2015
DOI: 10.1111/aas.12548
|View full text |Cite
|
Sign up to set email alerts
|

Obesity in regional anesthesia – a risk factor for peripheral catheter‐related infections

Abstract: This retrospective cohort study suggests that obesity is an independent risk factor for peripheral, but not neuraxial, catheter-related infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 35 publications
0
14
0
1
Order By: Relevance
“…Obesity also increases the risk of peripheral catheter-related infections under regional anesthesia. [14] In the current case, both ICB and SCB provided sufficient anesthesia in the surgical region. We initially planned to perform ICB or CCB because of the relatively low reported incidence of HDP.…”
Section: Retrospective Analysismentioning
confidence: 63%
See 1 more Smart Citation
“…Obesity also increases the risk of peripheral catheter-related infections under regional anesthesia. [14] In the current case, both ICB and SCB provided sufficient anesthesia in the surgical region. We initially planned to perform ICB or CCB because of the relatively low reported incidence of HDP.…”
Section: Retrospective Analysismentioning
confidence: 63%
“…Obesity also increases the risk of peripheral catheter-related infections under regional anesthesia. [ 14 ]…”
Section: Discussionmentioning
confidence: 99%
“…In another study, obesity was demonstrated to be an independent risk factor for catheter infections in PNBs but not for neuraxial blocks (69) . As adipose tissue is perfused poorly and subcutaneous tissue hypoxia occurs in obese people, the risk of wound infection increases with the decreased oxygen partial pressure.…”
Section: Catheter Placements and Site Infectionsmentioning
confidence: 94%
“…As a consequence, many of the following net-ra studies focused on the identification of risk factors for catheter-related infections. For example, odds for catheter-related infections are increased in diabetics (OR: 1.26, 95%CI: 1.02-1.55) [47] or in obese patients with peripheral catheters (OR: 1.69, 95%CI: 1.25-2.28) [48]. Moreover, the catheter-related infection profile over up to 15 days was determined in a cohort of 44,555 patients showing that infection risk starts to increase slowly at the fourth day after catheter placement [49].…”
Section: Big Data Initiatives In Acute Pain and Regional Anesthesia Researchmentioning
confidence: 99%